A PCR‐RFLP based test for distinguishing European and Atlantic sturgeons. (21st September 2013) - Panagiotopoulou, H.; Baca, M.; Popovic, D.; Weglenski, P.; Stankovic, A.
Summary The two sister species of Atlantic and European sturgeon are difficult to distinguish solely by morphological traits, especially in their early life stages. A simple PCR‐RFLP based test was developed, enabling easy identification of specimens belonging to both species. The application of two restriction enzymes (BtsI and BsrDI) allowed the clear and unambiguous discrimination of 132 specimens of Atlantic and European sturgeon. The test should prove particularly useful with regard to the sturgeon restitution programs currently underway on both sides of the Atlantic Ocean.